Making happy things : 20+ joyful and sustainable sewing projects - Lascelles, Sue-Ching (Hardie Grant Books, 2025)
"In this easy-to-follow guide, learn how to create more than 20 joyful DIY sewing projects out of repurposed materials. Known for her playful sense of style, Sue-Ching's projects will bring a smile to your face, whether it is her famous tea towel dress, a bandana cap or a prawn plush made out of scraps. This book is all about having fun, embracing the making process and creating unique, joyful garments that make you feel happy. In Making Happy Things Sue-Ching shares her passion for sustainability, repurposing and upcycling, encouraging us to reuse materials found at thrift stores or the linens at the back of your closet. This is your opportunity to breathe new life into old materials and gain practical insights into the art of re-purposing, guided by Sue-Ching's ingenious tips and ideas. Sue-Ching outlines the tools and materials you need, the core process to follow and sewing tips. Each project includes step-by-step instructions, and you can see each piece styled within the book. Making Happy Things will inspire you to be playful, inventive, and create a garment that you can wear with pride, confidence and authenticity - a true expression of your wonderful self!"--Publisher's description.